Navigational Chart of the North Atlantic Using an Oblique Conformal Map Projection - Gougenheim, André (The International Hydrographic Review, 2015)
The French Naval Hydrographic Office has recently published a navigational chart (No. 6504) of the northern portion of the Atlantic Ocean using an oblique conformal map projection. This chart, on a scale of about 1/6 000 000, is intended specifically for ships running between North America (from New York to Greenland) and the Eurafrican continental front (from Bergen to the Canary Islands), so that they may more easily make use of great circle tracks (figure 1). In the present article it is proposed, after recalling the problem posed by the plotting of great circle tracks on a navigational chart, to give the principal characteristics of the Hydrographic Office’s new chart, as well as the computation process used in its compilation.